Extensive regression in pigmented skin lesions: a dangerous confounding feature - Aimilios Lallas (Mattioli1885, 2012)
Spontaneous regression in melanomas is not an uncommon phenomenon, as it has been described in 10-35% of primary cutaneous lesions [1]. Regression does not appear to predict a more favorable course, since even fully regressed melanomas may progress into metastatic disease [2]. Several dermoscopic features have been correlated with the regression process, including white scar-like depigmented areas and gray-blue, pepper-like granules, which correspond to dermal scarring, pigment incontinence and presence of melanophages [3,4]. Regression may occur not only in melanomas, but also in melanocytic nevi, which similarly may exhibit white areas and gray-blue granules or areas under dermoscopy [5]. Overall, white areas have been proposed to be associated with the fibrosis type of regression and gray-blue areas to the melanosis type of regression of melanocytic tumors [3]. Lichen planus like keratosis (LPLK) is considered to represent a regressed solar lentigo or seborrheic keratosis. Dermoscopy of LPLK at the late stage of the regression process reveals a diffuse gray-blue granular pattern, similar to that observed in regressed melanocytic lesions [6].